Ultrasound‐assisted fractionation of dried distillers' grains with solubles (DDGS) at mild temperature for co‐production of xylan and protein feed. Issue 3 (5th December 2018) - Gu, Hanqi; Zhu, Yuyong; Li, Jie; Peng, Yanfang; Huang, Jinglu; Bi, Chunpu
Abstract: BACKGROUND: Ultrasound‐assisted fractionation of DDGS under mild conditions was proposed for extracting xylan from dried distillers' grains with solubles (DDGS) and recovering protein‐rich DDGS residue as animal feed. The composition and properties of xylan fractions and the DDGS residue obtained by ultrasound‐assisted extraction and those by a conventional method of alkaline extraction without ultrasound‐assistance were compared. RESULTS: Compared with the result for the conventional method, a similar xylan yield of 73.8% in the extracted liquid, but higher protein content of 26.2% in the DDGS residue were obtained by the ultrasound‐assisted process with NaOH at ultrasound power of 900W and 30 °C for 20 min. The ultrasound‐assisted process has a significant impact on the sugar composition and polysaccharide side chain and polymerization degree of the xylan fractions. The DDGS residue produced by the ultrasound‐assisted process had a fine porous structure as well as greater protein and essential amino acid content. The enzymatic hydrolysis of cellulose in DDGS residue reached 70% in the initial 3 h. CONCLUSION: Ultrasound‐assisted fractionation was an efficient process for comprehensive utilization of xylan and protein in the DDGS. The xylan fractions with lower polymerization degree were perfect feedstock for xylooligosaccharide production by enzymatic hydrolysis. The DDGS residue with adequate nutrition composition and efficient digestibility had potential advantages as an alternative animal feed to DDGS. © 2018 Society of Chemical Industry